2005
DOI: 10.1051/vetres:2004066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breed and gender on bovine liver cytochrome P450 3A (CYP3A) expression and inter-species comparison with other domestic ruminants

Abstract: -The cytochrome P450 (P450) superfamily represents a group of relevant enzymes in the field of drug metabolism and several exogenous or constitutional factors contribute to regulate its expression. Cattle represent an important source of animal-derived food-products and studies concerning the P450 expression are needed for the extrapolation of pharmacotoxicological data from one species to another and for the evaluation of the consumer's risk associated with the consumption of harmful residues found in foodstu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 55 publications
3
38
2
1
Order By: Relevance
“…Concerning CYP3A, both 6␤OH-T and 2␤OH-T activities pointed out significant differences among breeds, whereas ERDEM, ETDEM, and TAODEM ones did not. These contrasting results partially disagreed with those reported by Dacasto et al (2005), where significant differences, between PM and LIM cattle, were found for ERDEM, ETDEM, and 2␤OH-T. Out of ERDEM, whose protocol and the resulting catalytic activity in PM (the only used in both studies) were similar, methodological differences might be probably offered as a justification for such a discrepancy; for ETDEM, in terms of substrate concentration or instrument sensitivity; about 2␤OH-T, of more sensitivity and precision of the used method (HPLC). In this respect, the correlation analysis among catalytic activities and CYP3A4-like mRNA gave better coefficients with HPLC results, which indirectly suggest TST as a more specific and useful substrate to study CYP3A expression in cattle.…”
Section: Effect Of Breed Upon Drug-metabolizing Enzymes In Cattlecontrasting
confidence: 89%
See 2 more Smart Citations
“…Concerning CYP3A, both 6␤OH-T and 2␤OH-T activities pointed out significant differences among breeds, whereas ERDEM, ETDEM, and TAODEM ones did not. These contrasting results partially disagreed with those reported by Dacasto et al (2005), where significant differences, between PM and LIM cattle, were found for ERDEM, ETDEM, and 2␤OH-T. Out of ERDEM, whose protocol and the resulting catalytic activity in PM (the only used in both studies) were similar, methodological differences might be probably offered as a justification for such a discrepancy; for ETDEM, in terms of substrate concentration or instrument sensitivity; about 2␤OH-T, of more sensitivity and precision of the used method (HPLC). In this respect, the correlation analysis among catalytic activities and CYP3A4-like mRNA gave better coefficients with HPLC results, which indirectly suggest TST as a more specific and useful substrate to study CYP3A expression in cattle.…”
Section: Effect Of Breed Upon Drug-metabolizing Enzymes In Cattlecontrasting
confidence: 89%
“…In this respect, the correlation analysis among catalytic activities and CYP3A4-like mRNA gave better coefficients with HPLC results, which indirectly suggest TST as a more specific and useful substrate to study CYP3A expression in cattle. The immunoblotting, where the same anti-rat CYP3A1/2 cited by Nebbia et al (2003) was used, gave contradictory results compared with catalytic activities (according to Dacasto et al, 2005) but consistent with CYP3A4-like mRNA.…”
Section: Effect Of Breed Upon Drug-metabolizing Enzymes In Cattlementioning
confidence: 99%
See 1 more Smart Citation
“…CYP3A-dependent DME activity and cross-reacting proteins have been demonstrated in cattle (Dacasto et al, 2005), whereas a new isoform (CYP3A 37 ) has been sequenced and cloned in poultry (Ourlin et al, 2000). Members of the CYP3A subfamily metabolize a great number of drugs, as well as relevant endogenous compounds (e.g.…”
Section: Cyp3amentioning
confidence: 99%
“…CYP3A expression is induced by DEX, rifampicin, pregnenolone-16α-carbonitrile and phenobarbital (Cascales Angosto and Gómez-Lechón, 2004). Testosterone, erythromycin and ethylmorphine are generally recognised as CYP3A substrates, even in cattle (Dacasto et al, 2005;Machala et al, 2003;Sivapathasundaram et al, 2001;Szotáková et al, 2004). In vivo, the urinary 6β-hydroxycortisol/cortisol ratio has been identified as a suitable test for evaluating CYP3A activity (Galteau and Samsa, 2003).…”
Section: Cyp3amentioning
confidence: 99%